Adult education in the European Union - with a focus on Hungary - Szilvia Hámori (Hungarian Academy of Sciences, Institute of Economics, 2008)
This paper examines adult education in Hungary for the years 1999, 2001 and 2003 along three dimensions: (a) the fraction of individuals participating in adult education, (b) their demographic and socio-economic characteristics and (c) the probability of participating in adult education / adult education lasting less than one year in the framework of a logit model. In a second step the paper focuses on a cross-country comparison of the three areas described above based on the European Union Labour Force Survey (EU LFS). The international comparison covers nine EU Member States, namely, Belgium, Denmark, Estonia, Finland, Greece, Italy, Lithuania, Poland and Sweden.
Keywords: I21; C35; 330; Analysis of education; adult education; logit model; Bildung; Erwachsenenbildung; Ungarn; EU-Staaten